Digital Platforms for COVID-19 Vaccination Delivery - Ward, Gillan (World Bank, Washington, DC, 2021)
Digital solutions offer an opportunity to digitalize the vaccine delivery process, registration, and certification, making it more accurate, secure, effective, and connected with other health systems to provide a comprehensive view of the vaccination campaign. However, a lot of questions have been raised in terms of ethics, privacy, inequity, costs, and standards. These have made the case to create global standards and guidelines. These standards andguidelines should provide a response in terms of how to implement and not what specific solution to implement, taking into account the different country contexts, digital maturity, and needs. Any crisis of this scale inevitably attracts a large number of potential technology solutions—some highly innovative, some based on existing proven systems, some yet unproven, and some addressing underlying problems to enable better outcomes. This paper aims to help practitioners better understand the key capabilities of such digital systems and digital health solutions, the priorities for certain functionality, and how these systems may operate with existing country resources (e.g., Electronic Medical Record and Management Information Systems).